The Muslim Brotherhood’s ‘Virtuous society’ and State Developmentalism in Egypt: the Politics of ‘Goodness’ - Marie Vannetzel (Revue Internationale de Politique de Développement)
The rise of Islamists in Arab countries has often been explained by their capacity to offer an alternative path of development, based on a religious vision and on a parallel welfare sector, challenging post-independence developmentalist states. Taking the case of the Egyptian Muslim Brotherhood, and building on ethnographic fieldwork, this chapter aims to contribute to this debate, exploring how conflict and cooperation were deeply intertwined in the relationships between this movement and Mubarak's regime. Rather than postulating any structural polarisation, or—in contrast—any simplistic authoritarian coalition, the author argues that the vision of two models of development opposing one another unravels when we move from abstract approaches towards empirical studies. On the ground, both the Muslim Brotherhood and the former regime elites participated in what the author calls the politics of ‘goodness’ (khayr), which she defines as a conflictual consensus built on entrenched welfare networks, and on an imaginary matrix mixing various discursive repertoires of state developmentalism and religious welfare. The chapter also elaborates an interpretative framework to aid understanding of the sudden rise and fall of the Brotherhood in the post-2011 period, showing that, beyond its failure, what is at stake is the breakdown of the politics of ‘goodness’ altogether.